Incorporating Culture and Mother Tongue in Mathematics Learning : Counting Operation in Traditional Houses Using Banyuwangi - Hariastuti, Rachmaniah Mirza; Budiarto, Mega Teguh; Manuharawati, Manuharawati (Malikussaleh Journal of Mathematics Learning (MJML), 2020)
House of Using Banyuwangi is one of the cultural components of the Using tribe in Banyuwangi-Indonesia which contains a lot of mathematical concepts. The existence of mathematical concepts in culture, commonly known as ethnomathematics, can be the basis for the development of mathematics teaching materials for elementary school. In addition to the application of cultural components in the form of Using traditional houses, the use of Using language as a language of learning can also be a bridge for students to be able to more easily understand mathematical concepts that are still abstract.